The Professional Is the Personal: A Qualitative Exploration of Self-Care Practices in Clinical Infant Mental Health Practitioners. Issue 47 (8th October 2020) - Eaves, Tanika; Mauldin, Laura; Megan, Cora B.; Robinson, JoAnn L.
Abstract: Infant mental health (IMH) as an interdisciplinary field relies on relationships to heal past trauma and promote secure parent-infant attachment. Stress related to performing IMH work has gained more attention in workforce development/well-being literature. Yet, IMH workforce engagement in self-care practices to manage work stress is left unexplored. This qualitative investigation examines a purposive sample (N = 21) of clinical IMH practitioners in two U.S. states to answer the following research questions: a) What self-care practices do clinical IMH practitioners perform? b) Do clinical IMH practitioners rely on reflective supervision as a professional self-care practice? Data include: a) open-ended interviews with clinical IMH practitioners and b) an inventory measuring burnout. Results indicate that on average, the sample reported moderate to high levels of burnout. Yet the majority of the sample engaged in personal and professional self-care practices to manage work-related stress. Saturation of themes: a) heavy reliance on individual coping, b) reflective supervision is insufficient on its own, c) organizational supports may facilitate engagement in self-care and d) competing care demands impede self-care; suggests that individual engagement in self-care outside of work, may not sufficiently manage work-related stress in this group of social service professionals. Highlighted themes offer an ecological framework for considering the interplay between individuals and organizations in promoting IMH workforce well-being. Recommendations for systematic investigation of the role individuals and organizations play in promoting self-care practice and well-being in the broader IMH workforce, employing quantitative methods of inquiry are discussed.